OPTIMALISASI BUDAYA LITERASI (CALISTUNG) DALAM MENUMBUHKAN MINAT BACA SISWA KELAS VI SDIT INSAN KAMIL KOTA BIMA - Ine Kris Damayanti; Dewi Masitha; Hermansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The reading interest of the community, especially school children in Indonesia, is still very low. Education in Indonesia is still far behind when compared to developed countries. One indicator of successful education is students who have broad insight and knowledge. Students who have broad insight are students who like to read. The success of education is not measured by the number of students who get the highest score in a particular subject, but the number of students who like to read or commonly known as literacy. The success of education is not measured by the number of students who get the highest score in a particular subject, but the number of students who like to read or commonly known as literacy. This study aims to analyze the optimization of literacy culture of reading, writing, and writing and effective strategies in developing literacy culture in fostering reading interest in class VII students of SDIT Insan Kamil, Bima City. This study uses a qualitative research method with an Exploration Case Study approach. This approach has special attention to the phenomena studied, focuses on the activities of the research subjects, reveals problems, presents data, analyzes data, and obtains data through direct observation. The results of this study indicate that some students in grade VII of SDIT Insan Kamil, Bima City, still have a lack of interest in reading even though a reading literacy program has been held once a week. It can be concluded by researchers that when literacy activities are held in schools there are still students who are less interested in reading, what if literacy activities are not held. It is likely that the school will be far from advanced foreign schools and the generation that is born will be less qualified.